The Effect of Social connectedness and Mindfulness on Sustainable Wellbeing - Ninik Anggraini; Madha Komala; Dedi Purwana (AIBPM Publisher, 2019)
A global survey states that humans, in general, are increasingly happy globally. These results contradict the global situation where environmental disasters and global warming are increasingly threatening and making damage in various parts of the world. This, in turn, will result in unhappiness, at least in the long run. Because of this contradiction, sustainable wellbeing is raised, a more ethical concept, and hence, more essential for human welfare. The purpose of this study was to determine the effect of perceived job insecurity and mindfulness on sustainable wellbeing. This study used 140 employees in service center companies in Bekasi district and Karawang, The results show that social connectedness has a significant and positive effect on sustainable wellbeing. Mindfulness also has a significant and positive effect on sustainable wellbeing. The researcher uses the socio-ecological perspective as the grand theory to explain the relationship between the hypothesized relationships.